The Resurgence of Transnational Religious Non-State Actors in World Politics - Orogbemi, Elias Olajide (African Journal of Stability and Development (AJSD), 2018)
This paper focuses on the role which transnational religious non-state actors play in world politics. Conventionally, world politics has been organised around the principle of state sovereignty since the Peace of Westphalia in 1648. The overall point is that nearly all countries officially organise both domestic and international politics according to “secular” principles, that is, where religious beliefs do not significantly inform decision-making. The Peace of Westphalia secularised world politics by undermining religion and enshrined the territorially bounded sovereign state as the basic unit of world politics. This paper covers some salient issues as regards religious non-state actors and world politics. First, it discusses how the international system evolved in a highly secular fashion after the great wars of religion in the seventeenth century and how these secularising events were expressed in the academic study of world politics in the form of the secularisation thesis (the idea that religion is losing potency in shaping world politics). Second, this paper examines the rationale behind global resurgence of religion in the second half of the twentieth century. Third, it looks critically at misconceptions among scholars, political leaders, soldiers, and government bureaucrats as well as the role of religion in changing the landscape of world politics. Finally, this paper brings into focus the impact of transnational religious nonstate actors on world politics, with particular reference to the Catholic Church.